(untitled) (Indiana, 2004)
Introducing the most complete digital media reference available-more than 900 pages of fun and easy instructions and tips on digital photography, digital video, digital music, and CD and DVD recording. At under
Keywords: Digital media,Digital video,Photography,Truyền thông kỹ thuật số; Digital techniques